IMPLEMENTASI PROGRAM BELAJAR HINGGA MALAM HARI SEBAGAI BEST PRACTICE PENGEMBANGAN KURIKULUM DALAM MENINGKATKAN HASIL UJIAN SEKOLAH DI SD NEGERI SUKOMULYO KAPANEWON NGAGLIK SLEMAN YOGYAKARTA - Maria Sri Mulati; Dhiniaty Gularso (STKIP Subang, 2025)
This study aims to describe the implementation of the night study program as a best practice in curriculum development to improve elementary school students’ examination outcomes. The research was conducted at SD Negeri Sukomulyo, Ngaglik Subdistrict, Sleman Regency, Yogyakarta, involving 25 sixth-grade students. This study employed a qualitative descriptive approach using interviews as the primary data collection technique. The results indicate that the night study program contributes positively to improving students’ learning focus, understanding of subject materials, and overall examination performance. The program also strengthens collaboration between schools, teachers, parents, and the community in supporting student learning achievement. Therefore, the night study program can be considered an effective curriculum development best practice in elementary education.